New Partnerships for Old Sibling Rivals: The Development of Integrated Access Systems for the Holdings of Archives, Libraries, and Museums - Timms, Katherine (Archivaria, 2009)
This paper describes one avenue for beneficial and effective collaboration between the cultural heritage siblings of archives, libraries, and museums: creating integrated access systems. In the digital era, it is easier and more sensible to pool resources to provide streamlined and richer service to the clients of these institutions. Researchers are more likely to care about having access to a resource than knowing who owns it. After discussing the perceptions, similarities, and existing points of convergence between these types of institutions, this paper discusses various options for creating integrated access systems. These include: federated searching, metadata aggregation systems, the collection-level description method, and various hybrid systems. Although some issues and complications may need further resolution, the conclusion of the paper is that this type of partnership between sibling institutions is desirable and should be pursued for the benefit of the users. RÉSUMÉ Cet article décrit une piste de collaboration bénéfique et efficace pour les institutions du patrimoine culturel que sont les centres d’archives, les bibliothèques et les musées : la création de systèmes d’accès intégré. En cette ère numérique, il est plus facile et plus logique de mettre en commun les ressources pour fournir un service rationalisé pour les utilisateurs de ces institutions. Les chercheurs sont plus intéressés à accéder à une ressource qu’à se demander à qui elle appartient. Après avoir déterminé les perceptions, les similarités et les points de convergence existants entre les institutions culturelles, l’article explore les diverses options pour créer des systèmes d’accès intégré. Parmi celles-ci on trouve la recherche fédérée, les systèmes de métadonnées agrégées, la description au niveau de la collection et divers systèmes hybrides. Bien que certaines questions et certains problèmes nécessitent plus de travail, cet article conclut que ce genre de partenariat entre les institutions culturelles est souhaitable et qu’on devrait les poursuivre pour le bénéfice des utilisateurs.